Mathematical modelling analysis of diet planning for thalassemia patients / Siti Sarah Md Zulkifli and Siti Nor Nadrah Muhamad - Md Zulkifli, Siti Sarah; Muhamad, Siti Nor Nadrah (College of Computing, Informatics and Media, UiTM Perlis, 2023)
The purpose of this study is to develop a mathematical model of meal preparation for thalassemia patients. This study aims to find the cost of the food combinations, the amount of nutrients thalassemia patients needed, and the optimal model between linear programming and integer programming. The diet problem describes its limitations and objectives functions. Planning good meals requires taking into consideration a variety of constraints, including the required nutrient composition, the amount of food to be taken, and food allergy with the smallest cost possible. The formulation of mathematical models that correspond to all requirements and limitations. This article clarifies how the linear and integer programming approach provides an optimal and feasible solutions to the diet problem for thalassemia patients.